Evolution and application of airflow permeability characteristics of gob in roof cutting and pressure releasing mining method - Xiangjun Chen; Yunfei Du; Liang Wang; San Zhao (Energy Science & Engineering, 2020)
Abstract Cutting roof and release pressure technology has changed the pressure transmission mode of the roof and the caving characteristics of roof rock, which in turn has changed the permeability evolution of the gob. To obtain the permeability characteristics of the gob for the roof cutting and pressure releasing mining method, a mathematical model for the gob voidage and permeability was established by analyzing the overlying strata movement law and the lateral stress variation in the gob. The airflow migration law of haulage roadway 12 201 in Halagou coal mine was studied using Fluent software and an established mathematical model. The main conclusions obtained are as follows: The overburden pressure and lateral stress in the gob gradually increase with the advancement of the working face; along the direction of the retaining roadway, there are two roadway windflows entering the critical zones (the 22‐100 m and 390‐398 m sections). The inflow at these two sections accounted for 59% of the total air inflow, of which the most critical is the 28‐53 m section, which accounts for 43% of the total air inflow in the two severe air leakage sections. The findings of this work provide a theoretical basis for the implementation of antileakage technology in the gob under the roof cutting and pressure releasing mining method and help reduce the risk of spontaneous combustion in the gob.